2006
DOI: 10.1358/mf.2006.28.9.1003581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemotherapy or/and radiotherapy on survivin expression in ovarian cancer

et al.

Abstract: Survivin, a member of apoptosis protein inhibitor family, is upregulated in various malignancies, especially in chemotherapy- and/or radiation-resistant cell lines. In this study, the correlation between the level of survivin expression and degree of apoptosis was investigated in three ovarian cancer lines (two chemoresistant cell lines SKOV-3 and OVCAR-3, as well as one chemosensitive cell line OV2008) treated with 5 microg/ml of cisdiamminedichloroplatinum (cisplatin, CDDP) for 24 h, 2 Gy of (60)Co irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Importantly, survivin is commonly overexpressed in a wide variety of human malignancies, including gastric cancer [11,12]. Its expression in tumors is implicated in resistance to chemotherapy and radiotherapy [13,14], which was also confirmed in our previous reports [15,16]. Moreover, abundant studies have suggested that survivin is involved in occurrence and development of gastric cancerous invasion and/or metastasis [17][18][19][20].…”
Section: Introductionsupporting
confidence: 73%
“…Importantly, survivin is commonly overexpressed in a wide variety of human malignancies, including gastric cancer [11,12]. Its expression in tumors is implicated in resistance to chemotherapy and radiotherapy [13,14], which was also confirmed in our previous reports [15,16]. Moreover, abundant studies have suggested that survivin is involved in occurrence and development of gastric cancerous invasion and/or metastasis [17][18][19][20].…”
Section: Introductionsupporting
confidence: 73%
“…As an anti-apoptotic factor, survivin directly binds to and inhibits both caspase-3 and caspase-7 activity, leading to the arrest of apoptosis. Survivin expression may resist apoptosis induced by chemotherapy agents in tumor cells [34,35]. We suggest that the inhibition of survivin expression could activate caspases and contribute to gemcitabine inducing apoptosis in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 85%
“…27 The survivin promoter was a cisplatin or radiation-responsive promoter in ovarian cancer cells. 13,14 Cisplatin, a first-line cytotoxic agent, has been studied as an agent of single or combination regimen for ovarian cancer. Nonetheless, 50% to 70% of responders would relapse within approximately 18 months after the completion of the first-line therapy and would The ratio 3:2 or 3:1 is used to illustrate the potential additive or synergistic effects when CRAd-S.GRD was given in combination with cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The survivin promoter activity was reinforced with the treatment of cisplatin in cell lines of gli-oma and ovarian cancer as well as in primary tumor cells. 13 The replication of the CRAd agent CRAd-survivin was susceptible to a tumor-specific promoter survivin, which was stimulated by the treatment of cisplatin. Thus, the second possibility is of interest in that cisplatin could enhance the viral replication via the stimulation of the activity of the survivin promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation